ELT Students’ Attitudes towards Plagiarism in Writing Argumentative Essays - Happy Prasida Ningtyas; Bambang Yudi Cahyono; Niamika El Khoiri (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Plagiarism cases have increasingly occurred, especially in higher education, and Universitas Negeri Malang is one of universities in Indonesia that concerns about plagiarism cases. However, there are only a few studies concerning plagiarism that have been conducted in Universitas Negeri Malang. As EFL learners, ELT students are more likely to be exposed to plagiarism issues and might have committed plagiarism either intentionally or unintentionally. In order to prevent unexpected attitudes that may lead to plagiarism cases, this study used surveys to investigate the ELT students’ attitudes towards plagiarism in writing argumentative essays in terms of their behavioral, normative, and control beliefs. The subjects of the study were ELT students who were taking an Argumentative Writing course. The findings show that the majority of the ELT students have unfavorable attitudes towards plagiarism in writing argumentative essays. Even though some students show favorable attitudes and tend to approve plagiarism issues in certain situations, this study has confirmed that the students have generally understood about plagiarism, and they tend to perform unintentional plagiarism rather than intentional plagiarism. The favorable attitudes found in this study are mostly caused by the unclear information and policies concerning plagiarism, and the students’ competence in writing. Keywords: ELT students, attitudes, plagiarism, argumentative essays Abstrak: Kasus plagiarisme telah semakin marak, terutama di dunia pendidikan tinggi. Sebagai pelajar Bahasa Inggris sebagai Bahasa Asing (EFL), mahasiswa Pendidikan Bahasa Inggris (ELT) mungkin pernah melakukan tindak plagiarisme baik secara sengaja maupun tidak disengaja. Untuk mencegah sikap tidak terduga yang bisa mengarah pada masalah plagiarisme, penelitian ini bertujuan untuk menginvestigasi sikap mahasiswa ELT terhadap plagiarisme dalam menulis esai argumentatif dalam aspek sikap, normatif, dan kepercayaan kontrol. Penelitian ini menggunakan survei sebagai rancangan penelitian. Subyek penelitian adalah mahasiswa ELT yang sedang mengambil mata kuliah Argumentative Essay selama masa pengambilan data. Tiga aspek yang diukur dalam penelitian ini didasari oleh Teori Perilaku Terencana milik Ajzen dan Fishbein (1993). Hasil penelitian menunjukkan bahwa mayoritas mahasiswa ELT tidak mendukung adanya plagiarisme dalam menulis esai argumentatif. Hasil juga menunjukkan bahwa sikap mendukung terhadap plagiarisme bisa disebabkan oleh informasi dan peraturan mengenai plagiarisme yang tidak jelas, dan kompetensi mahasiswa dalam menulis. Meskipun beberapa mahasiswa menunjukkan sikap mendukung dan cenderung menyetujui masalah plagiarisme di situasi tertentu, penelitian ini menunjukkan bahwa secara umum mahasiswa telah memahami plagiarisme, dan mahasiswa yang menunjukkan sikap mendukung cenderung melakukan tindak plagiarisme secara tidak sengaja. Kata kunci: mahasiswa pendidikan bahasa Inggris, sikap, plagiarism, menulis, esai argumentative